PENGARUH EARNING PER SHARE (EPS), PRICE EARNING RATIO (PER) DAN PRICE BOOK VALUE (PBV) TERHADAP HARGA SAHAM EMITEN PERBANKAN INDEKS LQ45 DI BURSA EFEK INDONESIA TAHUN 2013- 2017 - Elan Nurhadi Purwanto; Suhari Pranyoto (Aliansi Perguruan Tinggi Badan Usaha Milik Negara (APERTI BUMN), 2019)
The purpose of this study examines the effect of Price Earning Ratio (PER), Price to Book Value Ratio (PBV) and Earning Per Share (EPS) on Stock Prices in banking companies listed on the Indonesia Stock Exchange, LQ45 index, in 2013-2017. This study is based on annual reports taken from the Indonesian Capital Market directory and other sources of support. The research sample was taken by purposive sampling technique with result in 5 banking issuers with 25 observation data and 5 cross section data. Data were analyzed by multiple regression techniques with the Ordinary Least Squared (OLS) approach. This study uses a panel data method with a fixed effect model by reviewing version 10. as a statistical tool. This study shows that PER, EPS and PBV have a positive and significant effect on stock prices simultaneously. Partially, PER has a positive and significant effect but PBV and EPS have a positive but not significant effect. The influence of PER significantly indicates that profitability is a priority consideration of investors rather than other factors.